The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/hec.3388
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Introducing a Minimum Price on the Distribution of Alcohol Purchase: A Counterfactual Analysis

Abstract: We use counterfactual analysis techniques to evaluate the impact of a $2 minimum unit price (MUP) on the distribution of Australian (Victorian) household off-trade alcohol purchases. Our estimates suggest that a $2 MUP significantly reduces the purchases of at-risk households by up to -0.92 [90% CI: -1.55, -0.28] standard drinks at the highest quantiles and has substantially less effect on households purchasing at light and moderate levels. A $2 MUP may reduce the proportions of male and female shoppers purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…The Sheffield Alcohol Policy Model is one such model and has been applied in England, 25–29 47 Scotland 45 51 and Canada 48 and provides very strong support for the specificity criterion. Further support is provided by other different modelling studies in the UK 49 50 and Australia 30 31 and a (non-randomised) trial in the USA. 41 Thus, support for the specificity criteria is very strong.…”
Section: Resultsmentioning
confidence: 92%
“…The Sheffield Alcohol Policy Model is one such model and has been applied in England, 25–29 47 Scotland 45 51 and Canada 48 and provides very strong support for the specificity criterion. Further support is provided by other different modelling studies in the UK 49 50 and Australia 30 31 and a (non-randomised) trial in the USA. 41 Thus, support for the specificity criteria is very strong.…”
Section: Resultsmentioning
confidence: 92%
“…Countries that currently use minimum unit pricing include Canada, Moldova, Russia, Scotland, Ukraine, Uzbekistan, and some US states (IAS 2019). MUP has been proposed as a way to target the population of heavy drinkers without penalizing light or moderate drinkers (Holmes et al 2014;Sharma et al 2016;Calcott 2019).…”
Section: Minimum Price Regulationmentioning
confidence: 99%
“…They find that moderate drinkers are barely affected regardless of income, while the heavy drinkers are most responsive to the minimum price adjustment, and the effects here are largest for the lowest-income drinkers. Sharma et al (2016) focus on Australia. Their simulation study evaluates the difference in the observed and counterfactual distributions of purchases based on whether or not a $2 MUP on alcohol is imposed.…”
Section: Minimum Price Regulationmentioning
confidence: 99%
“…First, the outlined hypothesis is longitudinal in nature and, hence, requires a longitudinal study to test it. Second, evidence regarding heavy drinkers' responsiveness to tax and price changes is inconclusive (Aepli, 2014;Byrnes, Shakeshaft, Petrie, & Doran, 2016;Elder et al, 2010;Sharma, Etile, & Sinha, 2016;Xuan, Chaloupka, et al, 2015). In addition, the differential impact of policy and availability changes, as a function of baseline drinking, is not well studied beyond price and tax studies.…”
Section: Relationships Tapered Offmentioning
confidence: 99%